In Focus: Capturing Female Rock Photojournalists Trailblazing Attitudes on Gender and Stereotypes (1970-1980s) - Bronsoms, Angels (Farol, 2024)
Women music photojournalists in the 80s escaped gender discrimination in the workforce because their work took place outside the newsroom. This finding merits an in-depth examination of women’s photojournalist perspective during this time. This paper provides a unique perspective by analyzing the gender perceptions of the participants’ professional experiences in photojournalism. The testimonies of five self-identified women, born between 1953 and 1963, who worked as music photographers between the 1970s and 1980s form the basis of this analysis. Their experiences offer valuable insight into the gender dynamics of the time. An analysis of the sample testimonies reveals that the public spaces where male and female photographers worked (e.g., concert halls, bars) had no significant impact on gender discrimination since editors worked with an economy of means compared to the work environments where men and women are forced to interact and socialize such as newsrooms. The findings of this study shed light on the gender dynamics in the music photography industry during the 1970s-1980s. They contribute to ethnographic research of subcultures and increase public interest in gender studies, particularly about education, professional performance, and perceptions of gender roles. The study underscores the need for further research and discussion on this topic.